(3GdegGQGJ GdSHGMI GdOhdjI s - (3YHO GdSdGe(B, (3eMQe fhMs ((3YeGf(B:s (3OGQ MGeO ddfTQ hGdJhRjY(B,s, 2019)
(3JfGhd gPG GdcJGH GdSHGMI cEMOi CfhGY GdQjGVGJ GdeGFjI ef fGMjI JGQjN GdJQHjI GdQjGVjI hCgejI GdSHGMI , EVGaI Gdi GdJMdjd Gdafj dSHGMI GdRMa Ydi GdHWf hGdRMa Ydi GdXgQ HGdHOA hGdOhQGf Ydi GdXgQ , ceG JfGhd HQfGeL JOQjH GdCfTWI GdMQcjI hJCKjQg Ydi eSJhi GdCOGA HGSJNOGe GdJeQjfGJ GdZQVjI, hJCKjQ GSJNOGe UOQjI GdSHGMI aj JWhjQ Yed GdPQGYjf hGdGfLGR aj SHGMI (B200(3e MQI dSHGMj CfOjI HZOGO ddCYeGQ (B13-14 (3SfI (B.s
(3GdeQGLY U(B.353s
Keywords: (3GdQjGVI GdeGFjI s